Globalization and governmentality in the post-colony: South Africa under Jacob Zuma - Thomas A. Koelble (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2018)
This paper addresses two twin questions - what accounts for the deep political and economic crisis in South Africa? The answer this paper develops is that both desired outcomes - a thriving capitalist economy and a solid democracy - were based on Western models and assumptions about the South African developmental trajectory that did not take into account the fact that few of the prerequisites for either outcome existed. By critically applying the work of Partha Chatterjee, I make the argument that around 60 per cent of South Africa's population is marginalized from both the capitalist economy and its democratic processes. As a result, this large population views both democracy and capitalism with disdain and mistrust. The "politics of the governed", as Chatterjee refers to it, is about access to scarce government-controlled resources and based on rules of exception where those who protest in the most effective (often violent) manner obtain access whereas those who occupy less strategic positions are ignored and forgotten. The politics of the governed takes place in a global setting in which the state is no longer economically sovereign and less able to distribute resources to achieve public goods. The combination of a large political society governed in a more or less democratic system and an open, capitalist economy produces a distinctive style of populist politics, corruption and violence.
Keywords: 320